INOVASI MEDIA PEMBELAJARAN PAI PADA MASA PANDEMI COVID-19 - Shirley Khumaidah; Mohammad Nu’man (TA'LIM : Jurnal Studi Pendidikan Islam, 2021)
During the Covid-19 pandemic which is still growing, making all elements of life have to undergo drastic changes. One of them is education, where learning that was previously carried out in person must be replaced with online learning. The method applied is qualitative, by including sources from books, articles, research, and the internet as references. The purpose of writing is to determine the renewal of PAI learning media to anticipate online learning. During the pandemic, some teachers choose to use online media as a renewal of the learning they are doing. The online media used by PAI teachers are WhatsApp, Zoom, Google Classroom, and Web which uses the internet as access.